2017
DOI: 10.1039/c7cc04295g
|View full text |Cite
|
Sign up to set email alerts
|

Solvent basicity promotes the hydride-mediated electron transfer doping of carbon nanotubes

Abstract: This study investigates the hydride-mediated electron transfer doping of single-walled carbon nanotubes using absorption spectroscopy and thermoelectric measurements. Specific solvent basicity is found to be important for the efficient n-type doping of carbon nanotubes. This progress is an essential requirement for the future development of electronic and energy devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In this context, several researchers have recently achieved such a thermoelectric property modulation using field effect and electrochemical transistor techniques [810]. We have also demonstrated the amphoteric (both p-type and n-type) chemical doping of SWNTs, achieving ambient stability and precise doping level control [1116]. …”
Section: Introductionmentioning
confidence: 99%
“…In this context, several researchers have recently achieved such a thermoelectric property modulation using field effect and electrochemical transistor techniques [810]. We have also demonstrated the amphoteric (both p-type and n-type) chemical doping of SWNTs, achieving ambient stability and precise doping level control [1116]. …”
Section: Introductionmentioning
confidence: 99%
“…We consider the thermoelectric properties of CNT films for elucidating their electronics tates at specific doping levels. [27][28][29][30][31][32][33][34][35] These complementary characterizations reveal that ionic and neutral surfactants afford p-typea nd n-type CNTs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared absorption spectroscopy is conducted to investigate the electronic structures. We consider the thermoelectric properties of CNT films for elucidating their electronic states at specific doping levels . These complementary characterizations reveal that ionic and neutral surfactants afford p‐type and n‐type CNTs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…2000 S cm −1 from ca. 500 S cm −1 films . Along with this, recent studies suggested that the encapsulation of dopants into SWCNTs might enhance doping efficiency that afford enhanced conductivity …”
Section: Figurementioning
confidence: 84%
“…500 S cm À 1 films. [12][13][14][15][16][17] Along with this, recent studies suggested that the encapsulation of dopants into SWCNTs might enhance doping efficiency that afford enhanced conductivity. [18,19] Herein we introduce advanced molecular dopants for the encapsulation inside SWCNTs.…”
mentioning
confidence: 99%